Ketahanan Pangan Rumah Tangga dan Kejadian Kurang Energi Kronis (KEK) pada Ibu Hamil Suku Anak dalam Desa Bungku Kabupaten Batanghari - Arnati Wulansari (Universitas Baiturrahim, 2020)
Chronic Energy Deficiency (CED) is the impact of poor nutritional status of pregnant women. One of determining factors that influence the nutritional status is household food security. The purpose of this study was to determine household food security and incidence of CED in pregnant women’s Suku Anak Dalam in Bungku Village Batanghari Regency. This study used crossectional study design and using a total sampling of 31 pregnant women. Measuring instruments using questionnaires and CED measured using CUA ribbon and energy intake 2x24 hours measuredby recall. Data analysis were used univariate and bivariate (spearman test). The results showed that the majority of respondent experienced the risk of CED(67.7%). As many as 45.2% household experienced food shortages. Most of respondent who experienced food shortages also have risk of CED was 25.8%. The results showed an correlation between food security and risk of CED (P<0.05).